Prevalence of antiphospholipid antibodies in patients with connective tissue diseases - Ruiz-Franco, Óscar Emilio (2011)
Objectives: To determine the prevalence of antiphospholipid antibodies in patients with connective tissue diseases. Design: Descriptive transversal study. Setting: Dos de Mayo Hospital and Institute of Clinical Research, San Marcos University, Lima, Peru. Participants: Patients with diagnosis of collagen disease and healthy subjects. Interventions: In 100 patients with collagen disease and 50 healthy subjects, all from Metropolitan Lima and attended between January and November 2008, fibrinogen, prothrombin time, partial activated thromboplastin time, anticardiolipin antibody and lupus anticoagulant were determined. Main outcome measures: Presence of anticardiolipin antibodies and lupus anticoagulant. Results: Patients with collagen diseases presented antiphospholipid antibodies in 17%, lupus anticoagulant in 13%, and IgG anticardiolipin in 4%. Individualizing connective tissue diseases, in 70 patients with systemic erythematous lupus 10 were positive for lupus anticoagulant and 3 had IgG anticardiolipin; of 30 patients with rheumatoid arthritis three were positive to lupus anticoagulant and one presented IgG anticardiolipin. In the group of 50 healthy individuals, only one was positive for lupus anticoagulant. Conclusions: The prevalence of antiphospholipid antibodies in patients with connective tissue was 17%. The most frequent connective tissue disease studied was lupus erythematosus and the most frequent antiphospholipid antibody found was lupus anticoagulant.